Activity of aldehyde dehydrogenase in B‐cell and plasma cell subsets of monoclonal gammopathy patients and healthy donors. (9th June 2016) - Všianská, Pavla; Bezděková, Renata; Kryukov, Fedor; Almáši, Martina; Pour, Luděk; Penka, Miroslav; Hájek, Roman; Říhová, Lucie
Abstract: Background: Aldehyde dehydrogenase (ALDH) is highly active in physiological stem cells as well as in tumor‐initiating cells of some malignancies including multiple myeloma (MM). Finding higher activity of ALDH in some cell subsets in monoclonal gammopathies (MG) could identify potential source of myeloma‐initiating cells (MICs). Methods: Bone marrow of 12 MM, 9 monoclonal gammopathy of undetermined significance (MGUS), and 10 healthy donors (HD) were analyzed by flow cytometry. ALDH activity of B‐cells and plasma cells (PC) was analyzed using Aldefluor. Results: Similar changes of ALDH activity were found during B‐cell development in HD and MG. Decreasing of ALDH activity from immature to naïve B‐cells was found. In postgerminal stages, the activity started to increase, and in PCs, the ALDH activity was the same as in immature B‐cells. Increased ALDH activity of all PC subsets compared to naïve B‐cells was found in MM as well as in HD, while in MGUS, only CD19 − PCs have higher ALDH activity. In HD, ALDH activity was higher in CD19 + PCs compared with MG. Conclusions: Our results indicate that changes of ALDH activity are the natural phenomenon in B‐cell development; thus, high ALDH activity as a single marker is not appropriate for MICs identification.